Importance of autophagy in colorectal cancer: A cross-sectional study - Sümbül, Hilmi Erdem; Akkız, Hikmet (Journal of Surgery and Medicine, 2019)
Aim: Colon cancer is the third most common cancer in women and men all over the world. Colorectal cancer (CRC) is diagnosed in over 1.2 million people globally each year. The disease is responsible for approximately 609,000 deaths a year (10% of all cancer cases in women and men). Autophagy is the basic catabolic mechanism that involves cell degradation of unnecessary or dysfunctional cellular components through the actions of lysosomes. The development of autophagy plays a great role in the pathogenesis of many diseases. It was found that autophagy could influence on tumor progression and stimulation. The purpose of this study is to determine the relationship between autophagy and autophagy related ATG5, ATG12, Beclin-1 gene and protein expressions and clinicopathological features of colorectal cancer. Methods: An observational study is planned. After approval of the ethical committee, the patients (n=45) operated for colorectal cancer was included to the study. There were totally 90 tissue samples taken and banked in liquid nitrogen: 1 tissue sample from tumor and 1 from normal from each patient. ATG5, ATG12, Beclin-1 gene expression levels in all samples were examined using SYBR- Green qPCR method, and, ATG5, Beclin-1, LC3 protein levels were analyzed using Western blotting technique. Expression levels were compared to clinicopathologic characteristics. Results: Gene and protein expression in both tumor and normal tissue equivalents were studied in most of the examples. There was no significant correlation between gene expression levels and demographic or clinicopathological features. The TNM stage of cases significantly correlated with perineural invasion and lymphovascular invasion. Conclusion: The results of this study suggest that autophagy may play a role in carcinogenesis of colorectal cancers. The further studies are required to determine the relationship between autophagy and clinicopathologic features associated with colorectal cancers.